2017
DOI: 10.1016/j.jsr.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

CDC's efforts to improve traumatic brain injury surveillance

Abstract: Introduction Youth sports concussion has become a prominent public health issue due to growing concern about the risk of long-term health effects. Method A broad spectrum of stakeholders has convened to propose solutions, including a committee of the National Academy of Sciences (NAS) who systematically examined the issue and, in a 2014 report, made a series of recommendations to better address this public health problem. Results Among these recommendations, the NAS committee called for CDC to develop a pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 12 publications
0
46
0
1
Order By: Relevance
“…The prevalence of concussions in the current study is higher than estimates based on emergency department data (e.g., 622.5 visits per 100,000 population aged 10–14 years) ( 5 ) and athletic trainer reports (e.g., 1.8 per 100 high school and college athletes for an average season) ( 6 ). Emergency department data miss concussions treated elsewhere, and athletic trainer reports miss concussions sustained outside of school-based sports; both sources miss medically untreated concussions ( 2 ). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of concussions in the current study is higher than estimates based on emergency department data (e.g., 622.5 visits per 100,000 population aged 10–14 years) ( 5 ) and athletic trainer reports (e.g., 1.8 per 100 high school and college athletes for an average season) ( 6 ). Emergency department data miss concussions treated elsewhere, and athletic trainer reports miss concussions sustained outside of school-based sports; both sources miss medically untreated concussions ( 2 ). …”
Section: Discussionmentioning
confidence: 99%
“…This study, and state-level YRBS data ( 4 ), support this conclusion by suggesting that many concussions among youths are not being counted and might also indicate that similar comprehensive estimates below the high school level are needed. To that end, CDC is working toward developing a National Concussion Surveillance System to determine the incidence and identify the circumstances of concussions, and all traumatic brain injuries, across the lifespan ( 2 ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of a national surveillance system, current efforts to collect data about the incidence of concussion via athlete self-report is needed (Bell, Breiding, & DePadilla, 2017). Wojtowicz, Iverson, Silverberg, Mannix, et al (2017) found that high school athletes reliably and consistently reported their concussion histories when they were surveyed during high school.…”
Section: Discussionmentioning
confidence: 99%
“…The CDC is currently pilot testing a concussion surveillance system to track, monitor, and accurately determine how many Americans sustain a concussion each year and how the injury happened (Bell et al, 2017). After a planned pilot phase is complete, the hope is to scale up to a national concussion surveillance system that will be administered on an ongoing basis.…”
Section: Discussionmentioning
confidence: 99%